Extension of Consultation Cycles Due to COVID-19 Pandemic. (Policy Papers; Policy Paper ;, 2020)
To better respond to the unprecedented demand from the membership for financing and crisis support in response to the covid-19 pandemic, there is a temporary postponement of staff's work on Article IV consultations and mandatory Financial Stability Assessments. To ensure the postponement has no adverse impact of members' compliance with their obligations, the deadlines for upcoming Article IV consultations and for discussions with currency unions have been extended by 6 months. This paper provides additional background on these temporary arrangements.